Rehabilitacija oseb s sindromom kronične razširjene bolečine - sindrom fibromialgije - Jamnik, Helena (Rehabilitacija (Ljubljana), 2010)
Chronic widespread pain/fibromyalgia (CWP/FS) is a common disorder among functional pain syndromes of undefined aetiology, associated with high direct medical costs and indirect costs such as sick leave and disability pension. Literature searches up to January 2010 of the US American National Guideline Clearing House, Medline and Cochrane Collaboration were conducted. Three evidence-based guidelines for the management of FS were identified: The American Pain Society (APS) (2005), the European League against Rheumatism (EULAR) (2007), and the Association of the Scientific Medical Societies in Germany (AWMF) (2008). Inconsistencies across guidelines were noticed, attributable likely to the differences in evidence categorisation and composition of the panels. APS and AWMF revealed the highest level of evidence for aerobic exercise, cognitive-behavioural therapy, amitriptyline, and multicomponent treatment, while EULAR identified highest level of evidence for a set of pharmacological treatments. The literature published subsequently to the guidelines demonstrated some more evidence for the effectiveness of certain pharmacological treatments, aerobic exercise and multidisciplinary treatment, and ineffectiveness of acupuncture.
Keywords: bolečina; fibromialgija; kronična bolečina; rehabilitacija; smernice; therapy; vocational rehabilitation; zdravljenje